Advances in fluid-structure interaction : updated contributions reflecting new findings presented at the ERCOFTAC Symposium on Unsteady Separation in Fluid-Structure Interaction, 17-21 June 2013, St John Resort, Mykonos, Greece /: updated contributions reflecting new findings presented at the ERCOFTAC Symposium on Unsteady Separation in Fluid-Structure Interaction, 17-21 June 2013, St John Resort, Mykonos, Greece. (2016) - Unknown
No abstract available